Experimental Study of Neuroprotective Properties of Inhaled Argon-Oxygen Mixture in a Photoinduced Ischemic Stroke Model - E. A. Boeva; D. N. Silachev; E. I. Yakupova; M. A. Milovanova; L. A. Varnakova; S. N. Kalabushev; S. O. Denisov; V. V. Antonova; I. A. Ryzhkov; K. N. Lapin; A. A. Grebenchikova (Общая реаниматология)
Acute ischemic stroke is a serious problem for healthcare systems worldwide. Searching for the optimal neuroprotector is a contemporary challenge. Various studies have demonstrated neuroprotective properties of argon in ischemic brain damage models. However, the published data are inconsistent.The aim of the study was to evaluate the effect of 24-hour argon-oxygen mixture (Ar 70%/O₂ 30%) inhalation on the severity of neurological deficit and the extent of brain damage in rats after a photoinduced ischemic stroke. Material and methods. The experiments were carried out on male Wistar rats weighing 430–530 g (N=26). Focal ischemic stroke was modeled in the sensorimotor cortex of the rat brain using photochemically induced vascular thrombosis. The animals were randomly divided into 3 groups: sham procedure + N₂ 70%/O₂ 30% inhalation (SP, N=6); stroke + N₂ 70%/O₂ 30% inhalation (Stroke, N=10); Stroke + Ar 70%/O₂ 30% inhalation (Stroke+iAr, N=10). The limb placement test (LPT) was used for neurological assessment during 14 days. Additionally, on day 14 after the stroke, brain MRI with lesion size morphometry was performed. Summarized for days 3,7 and 14 LPT scores were lower in the Stroke and Stroke + iAr groups as compared to the SP group.Results. Statistically significant differences in LPT scores between SP, Stroke, and Stroke+iAr groups were revealed on day 3 post-stroke: (scores: 14 (13; 14), 6.5 (4; 8), and 5 (3; 8), respectively, P=0.027). However, there was no statistical difference between the Stroke and Stroke+iAr groups.Conclusion. 24-hour inhalation of argon-oxygen mixture (Ar 70%/O₂ 30%) after stroke does not reduce the extent of brain damage or the severity of neurological deficit.